Pengaruh Kegiatan 5r, Motivasi, dan Pelatihan Terhadap Budaya Organisasi pada PT. Furukawa Optical Solutions Indonesia - Trianto, Eko; Agustiyani, Halimah Thusyadiyah; Masruri, Masruri (Lembaga Penelitian Universitas YARSI, 2024)
This study aims to evaluate the influence of 5R activities, motivation, and training on organizational culture. Determining the sample, the author used the purposive sampling technique, the population was 111 people and the sample was calculated using the Slovin formula rounded to 95 people. The data collection method was by distributing questionnaires. Structural Equation Modeling (SEM) was used as data analysis through the Partial Least Square (PLS) approach with Smart PLS 3.0 software. The results showed that the 5R activity variable had a positive and significant effect on organizational culture with p-values​​0.009 <0.05, the motivation variable did not have a significant effect on organizational culture with p-values​​0.435> 0.05, and training had a positive and significant effect on organizational culture with p-values​​0.000 <0.05. In addition, 5R activities, motivation, and training simultaneously influence organizational culture with a calculated f value of 30.3> F Table 2.70